Anosmia as an early symptom in patients with COVID-19: La anosmia como síntoma temprano en pacientes con COVID-19 - Huamán Navarro, Alex Stiven (2020)
From the time of knowledge of the outbreak appearance in mid-December 2019 due to the new coronavirus (SARS-CoV-2) in the city of Wuhan, China, epidemiologic and clinical studies have been developing to best define the symptomatology of the disease from coronavirus 2019 (COVID-19). However, within some significant reports, we have been informed that one of the initial symptoms of this disease can also be alterations in smell and taste (30 and 60% in the Korean and German series, respectively).